Lightweight flame-retardant thermal insulation material as well as preparation method and application thereof
By using water as a dispersion medium and hollow glass microbeads in lightweight insulation materials, combined with vibration mixing and sintering processes, the problems of microbead damage and insufficient performance of the matrix material are solved, and high-performance lightweight flame retardant is achieved Preparation and application of thermal insulation materials.
Patent Information
- Application Number
- CN202411716350.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-26
- Publication Date
- 2025-02-21
AI Technical Summary
When the filling amount of existing lightweight thermal insulation materials increases, hollow glass microbeads are prone to breakage, and the temperature and fire resistance of the matrix materials are insufficient, which limits the application range of the product.
Water is used as the dispersion medium, combined with hollow glass microbeads, sodium silicate, calcium carbonate and vapor phase silica, and lightweight flame retardant insulation materials are prepared through vibrating mixing and sintering processes to ensure uniform microstructure and good mechanical properties.
The microstructure of lightweight flame-retardant insulation materials has been uniform, good mechanical properties, low density, and improved thermal insulation and fire resistance. They are suitable for construction, ships and energy storage fields.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the field of flame retardant heat-insulating materials, in particular to a lightweight flame retardant heat-insulating material and a preparation method and application thereof. Background Art
[0002] Hollow glass microspheres are often added as functional fillers to matrix materials (such as resins, plastics, cement and coatings) due to their low density, high strength and good thermal insulation properties, and are made into lightweight thermal insulation materials through reaction curing. The greater the filling amount of hollow glass microspheres, the lower the density and thermal conductivity of the final product, so increasing the filling amount of hollow glass microspheres helps to improve the performance of lightweight thermal insulation materials. However, in conventional production processes, the greater the filling amount of hollow glass microspheres, the greater the breakage rate during the mixing process, making it difficult to achieve satisfactory results. On the other hand, due to the poor temperature resistance and fire resistance of the matrix material (especially organic materials) itself, the application range of the final product is also limited.
[0003] When only hollow glass microspheres are used to form products through sintering, although the damage of the microspheres caused by the mixing process of the matrix material and the microspheres can be avoided, and the heat resistance and fire resistance are enhanced due to the absence of organic components, the hollow glass microspheres have poor stacking properties in the air and it is difficult to evenly mix the solid phase of the microspheres and the sintering aid, resulting in poor mechanical properties of the final product, which cannot be used in fields with high requirements for structural strength. Summary of the invention
[0004] In view of this, the technical problem to be solved by the present invention is to provide a lightweight flame retardant thermal insulation material composition, a lightweight flame retardant thermal insulation material and a preparation method and application thereof. The lightweight flame retardant thermal insulation material provided by the present invention has uniform microstructure, good mechanical properties, low density, good thermal insulation performance and fire resistance.
[0005] The present invention provides a lightweight flame retardant heat insulating material, which is prepared from the following components:
[0006] Hollow glass microspheres: 20-100 parts by mass;
[0007] Water: 80-120 parts by weight;
[0008] Sodium silicate: 10-20 parts by mass;
[0009] Calcium carbonate: 5-15 parts by weight;
[0010] Fumed silica: 10-20 parts by mass.
[0011] Preferably, the lightweight flame retardant heat insulating material is prepared from the following components: hollow glass microspheres: 20-85 parts by mass; water: 80-120 parts by mass; sodium silicate: 10-20 parts by mass; calcium carbonate: 5-13 parts by mass; and fumed silica: 13-20 parts by mass.
[0012] In some embodiments of the present invention, the lightweight flame retardant thermal insulation material is prepared from the following components: hollow glass microspheres: 20-25 parts by mass; water: 80-90 parts by mass; sodium silicate: 18-20 parts by mass; calcium carbonate: 11-13 parts by mass; fumed silica: 13-15 parts by mass. The lightweight flame retardant thermal insulation material obtained by this formula has the lowest density and the best thermal insulation performance. Based on its mechanical properties, it is suitable for application in the field of energy storage.
[0013] In other embodiments of the present invention, the lightweight flame retardant heat insulating material is prepared from the following components: hollow glass microspheres: 55-65 parts by mass; water: 90-100 parts by mass; sodium silicate: 11-13 parts by mass; calcium carbonate: 7-9 parts by mass; fumed silica: 18-20 parts by mass. The lightweight flame retardant heat insulating material obtained by this formula has a relatively balanced density, mechanical properties and heat insulation properties, and is suitable for application in the construction field.
[0014] In other embodiments of the present invention, the lightweight flame retardant heat insulating material is prepared from the following components: hollow glass microspheres: 75-85 parts by mass; water: 110-120 parts by mass; sodium silicate: 10-12 parts by mass; calcium carbonate: 5-7 parts by mass; fumed silica: 15-17 parts by mass. The lightweight flame retardant heat insulating material obtained by this formula has high mechanical properties, high density and slightly low heat insulation performance, and is suitable for use in the field of ships with high safety requirements.
[0015] The lightweight flame retardant heat-insulating material provided by the present invention uses water as a dispersion medium, hollow glass microspheres as a heat-insulating material, and sodium silicate, calcium carbonate and fumed silica as sintering aids to prepare a lightweight flame retardant heat-insulating material with uniform microstructure, good mechanical properties, low density, good heat-insulating properties and fire-proof properties, which is suitable for application in various fields; wherein the true density of the hollow glass microspheres is 0.1 g / cm 3 ~0.7 g / cm 3 The median diameter D50 of the hollow glass microspheres is 30 μm to 70 μm. The apparent density of the lightweight flame retardant and heat insulating material of the present invention is 0.07 g / cm 3 ~0.35 g / cm 3 ; The thermal conductivity of the lightweight flame retardant thermal insulation material is 0.03 W / mK~0.20 W / mK.
[0016] The present invention provides a method for preparing the lightweight flame retardant thermal insulation material described in any of the above technical solutions, comprising the following steps:
[0017] Hollow glass microspheres, water, sodium silicate, calcium carbonate and fumed silica are vibrated and then sintered to obtain a lightweight flame-retardant thermal insulation material.
[0018] Specifically, hollow glass microspheres, water, sodium silicate, calcium carbonate and fumed silica are mixed in a mold to obtain a mold filled with materials; the mold filled with materials is then vibrated and then sintered to obtain a lightweight flame-retardant heat-insulating material.
[0019] The present invention firstly mixes hollow glass microspheres, water, sodium silicate, calcium carbonate and fumed silica in a mold without causing damage to the hollow glass microspheres. In certain embodiments of the present invention, the present invention uniformly mixes the hollow glass microspheres, water, sodium silicate, calcium carbonate and fumed silica in a low shear stirring kettle, and then pours the mixture into the mold to obtain a mold filled with materials.
[0020] After obtaining the mold filled with the material, the present invention vibrates the mold filled with the material. The frequency of the vibration of the present invention is 0.5 Hz to 50 Hz, and the vibration time is 5 min to 60 min. The present invention densifies the material through vibration, and at the same time, it is not easy to cause the hollow glass microspheres to be damaged.
[0021] The present invention vibrates the mold filled with the material and then sintering it to obtain a lightweight flame retardant thermal insulation material. The sintering described in the present invention is specifically: at -0.05 MPa~-0.1 MPa, the temperature is increased to 80℃~150℃ at a heating rate of 1℃ / min~10℃ / min and kept warm for 15 min~60 min; then at -0.05 MPa~-0.1 MPa, the temperature is increased to 600℃~850℃ at a heating rate of 1℃ / min~10℃ / min and kept warm for 15 min~60 min. The present invention sequentially desolventizes and sinters the material under negative pressure and high temperature conditions to form a lightweight flame retardant thermal insulation material, and obtains a lightweight flame retardant thermal insulation material product after the material is cooled and demolded.
[0022] The present invention also provides the use of the lightweight flame retardant thermal insulation material described in any of the above technical solutions as a building flame retardant thermal insulation material, a ship flame retardant thermal insulation material or an energy storage flame retardant thermal insulation material. The lightweight flame retardant thermal insulation material prepared by the method has a uniform microstructure, good mechanical properties, and an apparent density of 0.07 g / cm 3 ~0.35 g / cm 3 , thermal conductivity is 0.03 W / mK~0.20 W / mK, and fire resistance reaches A1 level. It can be used in construction, shipbuilding, energy storage and other fields.
[0023] The present invention provides a lightweight flame-retardant thermal insulation material and a preparation method and application thereof. The lightweight flame-retardant thermal insulation material provided by the present invention is prepared from the following components: hollow glass microspheres: 20 to 100 parts by mass; water: 80 to 120 parts by mass; sodium silicate: 10 to 20 parts by mass; calcium carbonate: 5 to 15 parts by mass; fumed silica: 10 to 20 parts by mass. The lightweight flame-retardant thermal insulation material provided by the present invention is made only of hollow glass microspheres and sintering aids and other inorganic materials, does not contain organic components, has uniform microstructure, good mechanical properties, low density, good thermal insulation and fire resistance, and an apparent density of 0.07 g / cm 3 ~0.35 g / cm 3 , thermal conductivity is 0.03 W / mK~0.20 W / mK, and fire resistance reaches A1 level, meeting application requirements in construction, shipbuilding, energy storage and other fields. DETAILED DESCRIPTION
[0024] The present invention discloses a lightweight flame retardant thermal insulation material and a preparation method and application thereof. Those skilled in the art can refer to the content of this article and appropriately improve the process parameters to achieve it. It is particularly important to point out that all similar substitutions and modifications are obvious to those skilled in the art, and they are all considered to be included in the present invention. The method and application of the present invention have been described through preferred embodiments, and relevant personnel can obviously modify or appropriately change and combine the method and application of this article without departing from the content, spirit and scope of the present invention to realize and apply the technology of the present invention.
[0025] The present invention will be further described below in conjunction with embodiments:
[0026] Example 1
[0027] The true density of 0.5 kg is 0.125 g / cm 3 , hollow glass microspheres with a median diameter D50 of 65 μm, 2 kg of water, 0.5 kg of sodium silicate, 0.3 kg of calcium carbonate and 0.35 kg of fumed silica were mixed evenly in a low shear stirred kettle and poured into a mold. The mold containing the material was placed on a vibration platform and vibrated at a frequency of 10 Hz for 20 minutes to densify the material. The mold containing the material was placed in a sintering furnace, and the temperature was raised to 120°C at a rate of 5°C / min under a negative pressure environment of -0.08 MPa and kept warm for 40 minutes; the temperature was raised to 650°C at a rate of 5°C / min under the same negative pressure environment of -0.08 MPa and kept warm for 60 minutes. After the material was cooled, it was demoulded to obtain a lightweight flame retardant and thermal insulation material product 1.
[0028] Example 2
[0029] The true density of 1.5 kg is 0.38 g / cm 3, hollow glass microspheres with a median diameter D50 of 40 μm, 2.5 kg of water, 0.3 kg of sodium silicate, 0.2 kg of calcium carbonate and 0.5 kg of fumed silica were mixed evenly in a low shear stirred kettle and poured into a mold. The mold containing the material was manually vibrated at a frequency of about 0.5-1 Hz for 5 minutes to densify the material. The mold containing the material was placed in a sintering furnace, and the temperature was raised to 150 ℃ at a rate of 10 ℃ / min under a negative pressure environment of -0.1 MPa and kept warm for 15 minutes; then the temperature was raised to 750 ℃ at a rate of 3 ℃ / min under a negative pressure environment of -0.06 MPa and kept warm for 30 minutes. After the material was cooled, it was demoulded to obtain a lightweight flame retardant and thermal insulation material product 2.
[0030] Example 3
[0031] The true density of 2 kg is 0.6 g / cm 3 , hollow glass microspheres with a median diameter D50 of 30 μm, 3 kg of water, 0.25 kg of sodium silicate, 0.15 kg of calcium carbonate and 0.3 kg of fumed silica were mixed evenly in a low shear stirred kettle and poured into a mold. The mold containing the material was placed on a vibration platform and vibrated at a frequency of 50 Hz for 5 minutes to densify the material. The mold containing the material was placed in a sintering furnace, and the temperature was raised to 80°C at a rate of 2°C / min under a negative pressure environment of -0.06 MPa and kept warm for 60 minutes; then the temperature was raised to 850°C at a rate of 10°C / min under a negative pressure environment of -0.08 MPa and kept warm for 15 minutes. After the material was cooled, it was demoulded to obtain a lightweight flame retardant and thermal insulation material product 3.
[0032] Comparative Example 1
[0033] The true density of 0.5 kg is 0.125 g / cm 3 , hollow glass microspheres with a median diameter D50 of 65 μm, 2.8 kg of epoxy resin and 0.4 kg of triethylenetetramine curing agent were mixed evenly in a low shear stirring kettle and poured into a mold. The mold containing the material was placed on a vibration platform and vibrated at a frequency of 10 Hz for 20 minutes to densify the material. The mold containing the material was left to stand, and after the epoxy resin and curing agent reacted and cured, demolding was performed to obtain comparative product 1.
[0034] Comparative Example 2
[0035] The true density of 2 kg is 0.6 g / cm 3, hollow glass microspheres with a median diameter D50 of 30 μm, 0.25 kg sodium silicate, 0.15 kg calcium carbonate and 0.3 kg fumed silica were mixed in a three-dimensional solid phase mixer and poured into a mold. The mold containing the material was placed on a vibration platform and vibrated at a frequency of 50 Hz for 5 minutes to compact the material. The mold containing the material was placed in a sintering furnace, and the temperature was raised to 850 ℃ at a rate of 10 ℃ / min under a negative pressure environment of -0.08 MPa and kept warm for 15 minutes. After the material was cooled, it was demoulded to obtain comparative product 2.
[0036] The apparent density, compressive strength, thermal conductivity, maximum applicable temperature and fire resistance of the products obtained in Examples 1, 2 and 3 and Comparative Examples 1 and 2 were tested, and the results are shown in Table 1:
[0037] Table 1
[0038]
[0039] From the above results, it can be seen that the fire protection level of the products in all embodiments reaches A1, among which: the product in Example 1 has the lowest density, the best thermal insulation performance, and the lower mechanical properties, and can be applied to the energy storage field; the product in Example 2 has relatively balanced density, mechanical properties and thermal insulation performance, and can be applied to the construction field; the product in Example 3 has higher mechanical properties, but higher density and lower thermal insulation performance than the products in other embodiments, and is suitable for application in the ship field with higher safety requirements.
[0040] Comparative Example 1 uses hollow glass microspheres of the same specifications as Example 1, but uses epoxy resin as a matrix and does not contain a sintering aid, and is formed after mixing and curing. Although the product of Comparative Example 1 has higher strength than the product of Example 1, it has a large apparent density, high thermal conductivity, low maximum applicable temperature, and low fire rating, and is not suitable for high temperature environments.
[0041] Comparative Example 2 and Example 3 use hollow glass microspheres of the same specifications, but do not use water as a dispersion medium. Instead, the microspheres and sintering aids are mixed in the solid phase, compacted by vibration, and then sintered by negative pressure. The product of Comparative Example 2 has similar thermal insulation and fireproof properties to Example 3, but due to the uneven mixing of the microspheres and the sintering aids and the loose stacking, its strength is relatively low, which limits its application in fields requiring high structural strength.
[0042] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. Lightweight flame retardant heat insulation material, characterized in that: It is prepared from the following components: Hollow glass microspheres: 20-100 parts by mass; Water: 80-120 parts by weight; Sodium silicate: 10-20 parts by mass; Calcium carbonate: 5-15 parts by weight; Fumed silica: 10-20 parts by mass.
2. The lightweight flame retardant heat insulating material according to claim 1, characterized in that: It is prepared from the following components: Hollow glass microspheres: 20-85 parts by mass; Water: 80-120 parts by weight; Sodium silicate: 10-20 parts by mass; Calcium carbonate: 5-13 parts by weight; Fumed silica: 13 to 20 parts by mass.
3. The lightweight flame retardant heat insulating material according to claim 1, characterized in that: It is prepared from the following components: Hollow glass microspheres: 20-25 parts by mass; Water: 80-90 parts by weight; Sodium silicate: 18-20 parts by mass; Calcium carbonate: 11-13 parts by weight; Fumed silica: 13-15 parts by mass; or, Hollow glass microspheres: 55-65 parts by mass; Water: 90-100 parts by mass; Sodium silicate: 11-13 parts by mass; Calcium carbonate: 7-9 parts by weight; Fumed silica: 18-20 parts by mass; or, Hollow glass microspheres: 75-85 parts by mass; Water: 110-120 parts by weight; Sodium silicate: 10-12 parts by mass; Calcium carbonate: 5-7 parts by mass; Fumed silica: 15-17 parts by mass.
4. The lightweight flame retardant heat insulating material according to claim 1, characterized in that: The true density of the hollow glass microspheres is 0.1 g / cm 3 ~0.7 g / cm 3 .
5. The lightweight flame retardant heat insulating material according to claim 1, characterized in that: The median diameter D50 of the hollow glass microspheres is 30 μm to 70 μm.
6. The lightweight flame retardant heat insulating material according to any one of claims 1 to 5, characterized in that: The apparent density of the lightweight flame retardant thermal insulation material is 0.07 g / cm 3 ~0.35 g / cm 3 ; The thermal conductivity of the lightweight flame retardant thermal insulation material is 0.03 W / mK~0.20 W / mK.
7. The method for preparing the lightweight flame retardant heat insulating material according to any one of claims 1 to 6, characterized in that: The following steps are involved: Hollow glass microspheres, water, sodium silicate, calcium carbonate and fumed silica are vibrated and then sintered to obtain a lightweight flame-retardant thermal insulation material.
8. The preparation method according to claim 7, characterized in that: The frequency of the vibration is 0.5 Hz to 50 Hz, and the time of the vibration is 5 min to 60 min.
9. The preparation method according to claim 7, characterized in that: The sintering is: At -0.05 MPa~-0.1 MPa, heat up to 80℃~150℃ at a heating rate of 1℃ / min~10℃ / min and keep warm for 15 min~60 min; then heat up to 600℃~850℃ at a heating rate of 1℃ / min~10℃ / min at -0.05 MPa~-0.1 MPa and keep warm for 15 min~60 min.
10. Use of the lightweight flame retardant and thermal insulation material according to any one of claims 1 to 6 as a building flame retardant and thermal insulation material, a ship flame retardant and thermal insulation material, or an energy storage flame retardant and thermal insulation material.
Citation Information
Patent Citations
Light heat-preservation heat-insulation material for marine deep water pipelines and preparation method thereof
CN104356606A
Lightweight noise-reducing composite material and preparation method thereof
CN108585942A
Composite hollow glass bead A-grade thermal insulation paste and preparation method thereof
CN114591027A
High-temperature-resistant mullite brick prepared from aluminum slag and preparation method of high-temperature-resistant mullite brick
CN118479868A
Composite thermal insulation material formed by lap joint of microspheres and preparation method therefor
WO2021136283A1